Vocabulary and reasoning abilities as correlates of secondary school students’ achievement in Yoruba esssay writing in Osun State, Nigeria (2022)
This study examined vocabulary and reasoning abilities as correlates of secondary school students ’ achievement in Yoruba essay writing in Osun State, Nigeria. The study adopted ex-post facto design of survey research type. The target population for the study comprised public and private senior secondary school II students. Simple random sampling technique was used to select four hundred students from ten secondary schools. The three instruments used for data collection are: Vocabulary Ability Test (r=0.82'), Reasoning Ability Test (r=0.89) and Yoruba Essay Writing Achievement Test (r=0.87). The study data was analyzed using the Pearson Product Moment correlation and Multiple regression analysis. Findings of the study revealed that the independent variables (vocabulary ability, reasoning ability) jointly predicted students' achievement in Yoruba essay writing (F(2,297) = 7.968; p<0.05). Furthermore, vocabulary ability contributed most with (ft = 0.158; t = 3.684; p<0.05) while reasoning ability did not contribute significantly to the model (f = 0.025; t = 0.498; p>0.05). The study recommended that vocabulary and reasoning abilities of the students should be given attention to by the teachers and parents, through thought-provoking ideas and questions. Schools should also encourage their students to participate in essay writing competitions organized within and outside the school premises